Alternating acid and alkaline diagenesis in the Shahejie Formation of E12 structure in the Laizhou Bay Sag, Bohai Bay Basin - Yang, Haifeng; Zhang, Shangfeng; Su, Ao; Guan, Dayong; Wang, Yaning; Su, Wen (Frontiers in Earth Science, 2023)
The high-quality reservoirs in the Shahejie Formation of the Laizhou Bay Sag, Bohai Bay Basin, Eastern China formed in the Paleogene saline lacustrine environment and show complex diagenetic evolutionary processes caused by alternating acid and alkaline fluids. Through observations under an optical microscope and a scanning electron microscope, casting thin sections, and plane porosity measurements, this study investigated the diagenesis differences in the third member of the Shahejie Formation (Es3 Member) in the root and central portions of a fan delta in the E12 structure in the eastern Laizhou Bay Sag, respectively. The Es3 reservoirs in the well A-1 which have no any hydrocarbon shows, are relatively tight, and have high argillaceous content, poor particle sorting, strong mechanical compaction, and intense carbonate cementation due to long-term activities of alkaline fluids. Moreover, they were not altered by organic acid due to the far lateral distance from source rocks. By contrast, the Es3 reservoirs in the well A-2 with hydrocarbon accumulations, contain an anomalously high porosity zone due to the superimposition of five episodes of alternate acid- alkaline fluids. The diagenetic fluids controlling the formation of the high-quality Es3 reservoirs are sourced from connate saline pore waters, gypsum dehydration , salt diapir, and organic acid. Moreover, chlorite coats in the reservoirs in the well A-2 inhibit secondary overgrowth of quartz and, thus, protect primary pores. The chlorite coats and alkaline-acid dissolution alterations are critical to the formation of the high-quality reservoirs in well A-2.